PENGARUH BEBAN KERJA, PERSEPSI DUKUNGAN ORGANISASI, DAN PENGEMBANGAN KARIR TERHADAP KEINGINAN BERPINDAH KERJA PADA KARYAWAN MR REALTY JAKARTA - Margaretha Vinna Supriyanto Supriyanto; Muhammad Alfan Khumaini; Awang Darmawan Putra; Agung Priyono (Journal of Management and Leadership, 2026)
This study aims to analyze the effect of workload, perceived organizational support, and career development on turnover intention among employees of MR Realty Jakarta. The research was conducted using a quantitative approach with associative research methods. Data were collected through questionnaires distributed to all 72 active employees of MR Realty Jakarta using a saturated sampling technique. The collected data were analyzed using SmartPLS. The results of the study indicate that workload has a positive and significant effect on turnover intention, meaning that higher workloads increase employees’ intention to leave the company. Perceived organizational support has a negative and significant effect on turnover intention, indicating that better organizational support can reduce employees’ intention to resign. Meanwhile, career development does not have a significant effect on turnover intention among MR Realty Jakarta employees. The findings also show that workload, perceived organizational support, and career development simultaneously explain 46.4% of turnover intention, while the remaining 53.6% is influenced by other factors outside this study. Therefore, companies are encouraged to manage employee workload effectively and improve organizational support to reduce turnover intention and maintain employee loyalty.